2020
DOI: 10.1021/acs.jafc.0c04925
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Storage-Related Oxidative/Hydrolytic Degradation of Olive Oil Secoiridoids by Liquid Chromatography and High-Resolution Fourier Transform Mass Spectrometry

Abstract: The study of negative effects potentially exerted by the exposure to oxygen and/or light and, thus, also by the type of container on the quality of extra virgin olive oil (EVOO) during its prolonged storage requires an appropriate choice of analytical methods and components to be monitored. Here, reverse-phase liquid chromatography coupled to high-resolution/accuracy Fourier transform mass spectrometry with electrospray ionization was exploited to study oxidative/hydrolytic degradation processes occurring on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Consequently, isoforms with a C 8 =C 10 bond should be present in olive oil also for oleacin and oleocanthal. This hypothesis has been recently confirmed in our laboratory using the same analytical approach described in the present paper, and, notably, open-structure isoforms with a C 8 =C 10 bond have been found to prevail in the chromatographic profiles obtained for the two secoiridoids [36].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Consequently, isoforms with a C 8 =C 10 bond should be present in olive oil also for oleacin and oleocanthal. This hypothesis has been recently confirmed in our laboratory using the same analytical approach described in the present paper, and, notably, open-structure isoforms with a C 8 =C 10 bond have been found to prevail in the chromatographic profiles obtained for the two secoiridoids [36].…”
Section: Discussionsupporting
confidence: 83%
“…Antioxidant properties are usually recognized for these compounds and ascribed to the presence of the phenolic OH group(s). On the other hand, as recently shown in our paper on secoiridoid alterations occurring upon prolonged storage of olive oil, their C=O groups are involved in oxidation to COOH groups, especially when open-structure isoforms are considered [ 36 ]. Such isoforms could then contribute significantly to the beneficial antioxidant properties of olive oil.…”
Section: Discussionmentioning
confidence: 99%
“…As recently evidenced for olive oil secoiridoids, whose profile is affected by various parameters, including olive cultivar and geographical origin [156], ripening stage at the harvesting time, agronomic and technological practices [157,158], and whose integrity was influenced by storage conditions [158], the distribution and integrity of phenolic compounds contained in OP and OOMW is expected to be affected as well. These differences are manifest when a comparison in quantitative terms is attempted (see Table 3).…”
Section: Olive Pomace (Op) and Olive Oil Mill Wastewater (Oomw)mentioning
confidence: 91%
“…It was demonstrated that the degradation rate of phenolic compounds during oil aging is strongly related to their initial concentration [13]. Some of the simple phenols, such as tyrosol and hydroxytyrosol, increase over time, likely owing to hydrolytic processes of secoiridoid derivatives representing their linked forms [14]. The percentage of hydrolysis typically increases in aged EVOO; therefore, the EVOO quality should be correlated to lower and not to higher values of tyrosol and hydroxytyrosol [15].…”
Section: Introductionmentioning
confidence: 99%